Efektivitas Modul Pembelajaran Berbantuan Software GeoGebra pada Materi Bangun Ruang Sisi Datar - Rhilmanidar Rhilmanidar; Marwan Ramli; Bansu Irianto Ansari (Didaktik Matematika, 2020)
The low learning outcomes of students on geometry may be due to the unavailability of GeoGebra software assisted learning modules. This research aims to investigate the effectiveness of a GeoGebra software assisted learning module on the theory of flat-faced 3D shapes. This study consists of three phases, which are preliminary research, prototyping phase, and assessment phase. The test subjects are the students of a junior high school in Aceh Selatan. The research instruments cover student activity sheets, formative test sheets, student response questionnaires, and observer response questionnaires. The results show that the learning module satisfies the effectiveness criteria. These results are supported by very good student activities, improvement in students score of formative test, and positive responses of the students and teachers on the learning module.